Helicobacter pylori and its effect on the body. Worldwide prevalence of Helicobacter pylori - Shukhtina, I.; Shukhtin, V.; Gozhenko, A.; Avramenko, A.; Badiuk, N. (Journal of Education, Health and Sport, 2016)
Helicobacter Pylori is one of the most common bacteria in the world's population, mainly causing chronic gastritis, which can progress to such severe complications as gastric and duodenal ulcers, gastric adenocarcinoma, and gastric MALT lymphoma.The bacterium Helicobacter Pylori is highly prevalent in a wide variety of countries around the world. Not only the adult population suffers from helicobacteriosis, but also children from birth whose parents are carriers or have symptoms of helicobacter infection. Helicobacter Pylori is a very capricious bacterium in cultivation, which requires a special composition of the nutrient medium, its optimal pH and temperature regime. Helicobacter Pylori produces a wide range of enzymes, urease is one of the many enzymes on which diagnostic methods are based.